Penile fracture with bilateral corporeal rupture without urethral involvement - Yonguc, Tarik; Bozkurt, Ibrahim Halil; Ors, Bumin; Kozacıoglu, Zafer; Arslan, Burak; Yonguc, Nilufer Goksin (Canadian Urological Association Journal, 2014)
Concomitant urethral injury is rare in penile fracture. We report the case of a 34-year-old male who presented to the emergency department 12 hours after a blunt self-injury of the penis. Physical examination revealed a swollen, ecchymotic, and deviated circumcised penis without blood at the meatus. The fracture line extending along the bilateral corpora without urethral involvement was seen intraoperatively. The fracture side was repaired primarily. The patient healed and recovered without complication. To our knowledge, this is the second reported case of bilateral corporeal rupture without urethral involvement.